Disulfiram in glioma: Literature review of drug repurposing - Zhong, Shiyu; Shengyu Liu,; Xin Shi,; Zhang, Xudong; Li, Kunhang; Liu, Guojun; Li, Lishuai; Tao, Shanwei; Zheng, Bowen; Sheng, Weichen; Ye, Ziyin; Xing, Qichen; et al. (Frontiers in Pharmacology, 2022)
Gliomas are the most common malignant brain tumors. High-grade gliomas, represented by glioblastoma multiforme (GBM), have poorer prognosis and are prone to recurrence. The standard treatment strategy is removal of tumor combining with radiotherapy and chemotherapy such as temozolomide (TMZ). However, even after conventional treatments, they still have a high recurrence rate, resulting in an increasing demand for effective anti-glioma drugs. Drug repurposing is a method of reusing drugs that are already widely approved for new indicative areas. It has the advantages of reduced research costs, safety, and increased efficiency. Through drug repurposing, disulfiram (DSF), originally approved for alcohol dependence, has been repurposed for adjuvant chemotherapy in glioma. This article reviews the method of drug repurposing and the progress of research on the reuse of disulfiram for glioma.